The Integrated Strategic-Behavioural Framework (ISBF): Synthesizing Dynamic Capabilities, Resource Management, and Self-Efficacy for Enhanced Competitiveness in Indonesian Language Skill Training Centers (LSTCs) - Tatang Sutarman; Yayan Hendayana (Dinasti International Journal of Education Management and Social Science, 2025)
This research proposes the Integrated Strategic-Behavioural Framework (ISBF) to enhance the competitiveness of Indonesian Language Skill Training Centers (LSTCs) that prepare Migrant Workers (PMI). Current LSTCs suffer from a performance gap, failing to meet high international skill demands, unlike competitors like Vietnam. The framework argues that sustained competitiveness is achieved not by possessing resources alone, but by dynamically aligning internal resources with external demands (DC bridging RBV and RDT) while ensuring optimal individual performance (SCT) under an ethical mandate (CPT). The study recommends LSTCs prioritize intangible asset investment and institutionalize dynamic adaptation routines to elevate Indonesia's position in the global skilled labour market.